Odpowiedzi

2009-12-23T14:48:25+01:00
X*+y*+6x-16=0
x-2y=2
-2y=2-x => 2y=x-2 => y=(2-x)/2

x* + (2-x)*/4 +6x -16 = 0
x* + (4 -4x + x*)/4 +6x -16 = 0
(4x*+4-4x+x*+24x-64)/4=0
4x*+x*+24x-4x+4-64=0
5x* + 20x - 60 = 0
∧ = 20^2 + $*5*60 = 1600
√∧ = 40

X1 = (-20 + 40) / 10 = 20/10 = 2
X2 = (-20 - 40) / 10 = -60/10 = -6
2009-12-23T14:52:37+01:00
(2 + 2y)² + y² + 6 * (2 + 2y) - 16 = 0
x = 2 + 2y

4 + 8y + 4y² + y² + 12 + 12y - 16 = 0
x = 2 + 2y

5y² + 12y = 0
x = 2 + 2y

y (5y + 12) = 0
x = 2 + 2y

dla y = 0

y= 0
x = 2

dla 5y + 12 = 0

y = -2,4
x = -2,8
2009-12-23T19:59:59+01:00
X=2+2y
(2+2y)² + y² + 6(2+2y) - 16 = 0

4 + 8y + 4y² + y² + 12 +12y -16 = 0
5y² +20y=0

Δ= 400
√Δ = 20

x1 = (-20 - 20) / 10 = -40/10 = -4
x2 = (-20 + 20) / 10 = 0 / 10 = 0

-4 - 2y= 2
-6 = 2y / 2
y = -3

lub

0 - 2y = 2
-2 = 2y /2
y = -1